2016
DOI: 10.1038/srep32865
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel sesquiterpene biosynthetic machinery involved in astellolide biosynthesis

Abstract: Esterified drimane-type sesquiterpene lactones such as astellolides display various biological activities and are widely produced by plants and fungi. Given their low homology to known sesquiterpene cyclases, the genes responsible for their biosynthesis have not been uncovered yet. Here, we identified the astellolide gene cluster from Aspergillus oryzae and discovered a novel sesquiterpene biosynthetic machinery consisting of AstC, AstI, and AstK. All these enzymes are annotated as haloacid dehalogenase-like h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 44 publications
2
52
0
Order By: Relevance
“…1990 ), aspergillomarasmins ( Robert et al., 1962 , Barbier et al., 1963 ), asperopterin A & B ( Matsuura et al . 1972 ), aspirochlorins ( Sakata et al., 1983 , Champhamjon et al., 2014 ), cyclopiazonic acid and speradines ( Orth, 1977 , Tokuoka et al., 2015 ), 14-deacetyl parasiticolide A & B and dideacetyl parasiticolide A, confertifolin, dideacetyl astellolide A & B ( Rank et al., 2012 , Shinohara et al., 2016a , Shinohara et al., 2016b ), 13-desoxypaxilline ( Rank et al . 2012 ), ditryptoleucine ( Rank et al .…”
Section: Resultsmentioning
confidence: 99%
“…1990 ), aspergillomarasmins ( Robert et al., 1962 , Barbier et al., 1963 ), asperopterin A & B ( Matsuura et al . 1972 ), aspirochlorins ( Sakata et al., 1983 , Champhamjon et al., 2014 ), cyclopiazonic acid and speradines ( Orth, 1977 , Tokuoka et al., 2015 ), 14-deacetyl parasiticolide A & B and dideacetyl parasiticolide A, confertifolin, dideacetyl astellolide A & B ( Rank et al., 2012 , Shinohara et al., 2016a , Shinohara et al., 2016b ), 13-desoxypaxilline ( Rank et al . 2012 ), ditryptoleucine ( Rank et al .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the drimane synthase is likely to be different from the commonly observed sesquiterpene synthase, which belongs to the class I terpene synthases. Recently, the drimane synthase AstC involved in biosynthesis of the astellolides was identified and shown to be a novel member of the terpene synthase family, showing similarity to haloacid dehalogenase (HAD)-like hydrolases [21]. Thus, we suspected that a related enzyme may be involved in the biosynthesis of the nanangenines, and used the amino acid sequence of AstC to probe the A. nanangensis genome.…”
Section: Resultsmentioning
confidence: 99%
“…AstC, though annotated as a HAD-like hydrolase and having low sequence homology to other characterised terpene synthases, contains sequence motifs conserved across both class I (DDxxD/E) and class II (DxDD, QW) terpene synthases [3335]. Specifically, AstC contains a DxDTT motif [21], which is a variant of the DxDD motif known to be involved in class II-type protonation-initiated terpene cyclisation [36]. Importantly, the DDxxD motif in AstC contains a substitution of the second Asp for Asn, leading to a loss of ionisation-activated cyclisation activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These HAD-like proteins harbor a DxDTT motif, which is a variant of the DxDD found in Class II diTS [ 95 , 96 ]. Shinohara et al [ 97 ] reported that some sesquiTS can contain HAD-like domains and DxDTT motifs, leading to FPP cyclization through a protonation step, instead of by an ionization step. We hypothesized that HAD-like TSs might be particular bifunctional sesquiTS, synthesizing specific metabolites of Viride clade.…”
Section: Discussionmentioning
confidence: 99%